1986
DOI: 10.1073/pnas.83.17.6238
|View full text |Cite
|
Sign up to set email alerts
|

The pseudopterosins: anti-inflammatory and analgesic natural products from the sea whip Pseudopterogorgia elisabethae.

Abstract: The Caribbean sea whip Pseudopterogorgia elisabethae (Octocorallia, Cnidaria) has been found to contain the pseudopterosins, a newly described class of natural products, which have been characterized as diterpene-pentoseglycosides. The pseudopterosins possess anti-inflammatory and analgesic properties that exceed, in our assays, the potencies of existing drugs such as indomethacin. As anti-inflammatory agents, the pseudopterosins appear to modify the arachidonic acid cascade by an as yet undefined mechanism of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
131
0
5

Year Published

1994
1994
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 194 publications
(138 citation statements)
references
References 6 publications
2
131
0
5
Order By: Relevance
“…The first indication that this unwanted isomerization can be completely blocked and exclusive selectivity for the 20 (S) compound can be achieved came from ligands L5 (RaScSc) and L10 (ScSc), which give a clean mixture of 5 and 6, with no trace of the 20 (R)-epimer 7, the 1,4-adduct 8 or isomerization products (eq 2, entries 3 and 5−8). Typically, the reaction is done as follows: a solution of 0.0025 mmol of [(allyl) 2 NiBr] 2 in 0.5 mL of solvent (usually CH 2 Cl 2 ) and a solution of the ligand in 0.5 mL solvent are mixed in a drybox. This solution is added to a suspension of Na BARF (1 equiv with respect to Ni).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The first indication that this unwanted isomerization can be completely blocked and exclusive selectivity for the 20 (S) compound can be achieved came from ligands L5 (RaScSc) and L10 (ScSc), which give a clean mixture of 5 and 6, with no trace of the 20 (R)-epimer 7, the 1,4-adduct 8 or isomerization products (eq 2, entries 3 and 5−8). Typically, the reaction is done as follows: a solution of 0.0025 mmol of [(allyl) 2 NiBr] 2 in 0.5 mL of solvent (usually CH 2 Cl 2 ) and a solution of the ligand in 0.5 mL solvent are mixed in a drybox. This solution is added to a suspension of Na BARF (1 equiv with respect to Ni).…”
Section: Resultsmentioning
confidence: 99%
“…Consider for example, precursors (e.g., 1) for calcitriol analogs with exocyclic C 20 (S)-configuration, which have been shown to have significant biological activity. 9 These molecules are currently prepared by circuitous routes that involve the equilibration of the aldehyde 2, obtained from vitamin D 2 and subsequent reactions of the minor isomer isolated from the mixture. 10 We recently showed 11 that the asymmetric hydrovinylation of readily available 1-vinylcycloalkene offers a potential general solution to this exo-cylic stereochemistry problem (Scheme 1).…”
Section: Introductionmentioning
confidence: 99%
“…The Caribbean gorgonian Pseudopterogorgia elisabethae is the source of potent antiinflammatory agents, the pseudopterosins (Look et al 1986a;Look et al 1986b). Evidence suggests that the biosynthetic machinery for pseudopterosin biosynthesis is located in P. elisabethae's symbiont, the dinoflagellate Symbiodinium sp.…”
Section: * Corresponding Authorsmentioning
confidence: 99%
“…Recent studies o f marine invertebrates have shown that they contain substances, many of which are defensive compounds, with significant potential for treatment of many human diseases. Marine invertebrate animals have already yielded substances that appear promising for the treatment of cancer (de Silva and Scheuer, 1980;Rinehart et at., 1981;Look et al, 1986).…”
Section: Techniques To Address T H E Scientific Questionsmentioning
confidence: 99%